PEACEKEEPING AND THE PROTECTION OF CIVILIANS from moral imperative to effective practice. - Donais, Timothy (ROUTLEDGE, 2025)
This book critically examines the evolution of protection practices in UN peace operations over the past two decades.Protecting civilians has become central to the work of contemporary UN peace operations, yet the ability of peacekeepers to offer meaningful levels of protection to vulnerable civilians in conflict zones remains highly circumscribed. Focusing on the implementation of protection of civilians (PoC) mandates across three high-profile UN missions - UNMISS in South Sudan, MONUSCO in the Democratic Republic of the Congo and MINUSCA in the Central African Republic - this study asks who precisely UN peacekeepers protect and how they go about protecting them. Drawing on the key distinction between coercive and non-coercive protection strategies, this book examines how peacekeepers have struggled to translate ambitious and far-reaching protection mandates into effective protection practices in some of the world's most dangerous and difficult conflict contexts. This book will be of much interest to students of peacekeeping, civilian protection, African politics, war studies and security studies.
Keywords: United Nations -- Peacekeeping forces.; Peacekeeping forces (International law); Civilians in war.; elektronické knihy; electronic books